The decline of British industrial hegemony - Ray, Indrajit, author.
1 online resource.
Keywords: "Through two World Wars and the Great Depression, this book explores the turbulent history of colonial Indian industry in the period immediately prior to independence. Focusing on five major industries in Bengal - coal mining, iron-smelting, jute manufacturing, paper making and tea plantation - the book looks at the impact of the war efforts on production, employment and capital: some industries experienced rapid growth due to additional investment, others suffered due to the dislocation of markets. Moreover, by drawing lessons from the war economy (especially the dearth of various essential commodities including war materials), the colonial government took up various measures in the inter-war period to promote India's domestic industries for the first time. Additionally, the book also argues that many of the expatriate firms in India became financially weak because of the Depression which paved the way for the 'Indianisation' of corporate houses. These elements were significant factors in the decline of British industrial hegemony in India and aided the de-colonisation process which followed. This book will be of interest to scholars of Indian economic history as well as those with wider interests in decolonisation, industrial history and the first half of the twentieth century"--